Drug repurposing for Alzheimer’s disease: in silico and in vitro investigation of FDA-approved drugs as acetylcholinesterase inhibitors - Kumar N.; Gahlawat A.; Kumar R.N.; Singh Y.P.; Modi G.; Garg P. (My University, 2025)
Alzheimer’s disease (AD) is one of the most familiar multifactorial and complex neurodegenerative disorders characterized by loss of cholinergic neurons in the brain. The various attempts for drug development to treat AD have been hampered by largely unsuccessful clinical trials in the last two decades. Developing a new drug from scratch takes enormous amounts of time, effort and money, mainly due to several barriers in the therapeutic drug development process. Drug repurposing strategy resuscitates this slow drug discovery process by finding new uses and clinical indications for existing drugs. This study is focused on the cholinergic hypothesis, a well-established target of the clinically available drugs in the market for the treatment of AD. The computational virtual screening (VS) led to the identification of thiazolidinedione (TZD, antidiabetic) and aminoquinoline (antimalarial) class of drugs as acetylcholinesterase (AChE) inhibitors. Intriguingly, rosiglitazone (RGZ) and hydroxychloroquine (HCQ) were found to be mild-to-moderate inhibitors of hAChE (human acetylcholinesterase) in our enzyme inhibition studies which are complementary to our computational studies. On the basis of our computational and experimental studies, it can be suggested that the beneficial effect of RGZ and HCQ in AD patients reported in the literature may partly be due to their AChE inhibitory property. The VS also led to the identification of antifungal drugs miconazole and oxiconazole as potential AChE inhibitors. The molecular dynamics (MD) simulation of the potential hits belonging to TZD, aminoquinoline and azoles class were also carried out. The MD simulations studies revealed detailed computational insights related to molecular interactions and protein–ligand stability for selected hits. © 2020 Informa UK Limited, trading as Taylor & Francis Group.